Using precision polymer chemistry for plastics traceability and governance. Issue 43 (21st October 2022) - Johnson, Hope; Chambers, Lewis C.; Holloway, Joshua O.; Bousgas, Annastasia; Akhtar-Khavari, Afshin; Blinco, James; Barner-Kowollik, Christopher
Abstract : Resolving the anonymity of plastic materials is critical for safeguarding the well-being of our natural environments and human health. Abstract : Resolving the anonymity of plastic materials is critical for safeguarding the well-being of our natural environments and human health. Herein, we explore how contemporary polymer chemistry – in the form of sequence-defined polymers and their enormous information depth potential, fused with progress in law and governance research – has the potential to significantly impact design standards, consumer behaviour, recycling systems and extended-producer responsibility schemes for plastic waste. We submit that chemistry and law need to work together in a true transdisciplinary effort to effectively combat the critical issue of plastic pollution.